DUTY OF MEMBER STATES OF UNITED NATIONS ORGANIZATION TO PROSECUTE INTERNATIONAL CRIMES; A CRITICAL ANALYSIS - Oguno, Prof. P. E. O.; Emmanuel, Emone (American Journal of Law, 2019)
The United Nations Organization is a very delicate organization. It has no standby army yet it is charged with the huge responsibility of prosecuting International Crimes. It is evident that it cannot succeed in this noble assignment without the cooperation of it's member states. The aim of this paper is to portray how the Member States of United Nations Organization aids the United Nations Organization in ensuring a world devoid of international crimes. The researcher discovered that most of the member states are loyal to this mission of the United Nations Organization. The loyalty of the member States could be seen in their cooperation with the International Criminal Court whose ultimate mandate is to prosecute Genocide, War Crimes, Crimes against Humanity and aggression. These are major International Crimes that are threatening the Peace and Prosperity of the world. The duty of these member states will be explained below and recommendations for efficient discharge of duty of the member states of United Nations Organization will be given by the researcher.